Ragioni d'amore - Luigi, Totaro (Firenze University Press, 2005)
This text proposes a rereading of the Decameron that traces the female figures - 'constrained' as we are told in the Proem, by the 'wishes', 'desires' and 'orders' of fathers, mothers, brothers and husbands - in their attempt to open up areas of personal life. The possession of the female body, considered as part of the family property in a social context governed by a commercial rationale, is an instrument of the violence characterising all social relations, which Boccaccio indicates as a cause for the wrath of God that exploded in the plague of 1348. Moreover, their bodies also become an instrument in the hands of the women themselves when they decide - with all the ambiguity which the context imposed (even on the author) - to repossess the same to use it as a weapon of revenge, an occasion of joy or a gift of love.